Od Atatürka do Erdoğana – ewolucja roli religii w Turcji w okresie rządów AKP - Szkudlarek, Magdalena (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The aim of this article is to provide an answer to the question whether or not Recep Tayyip Erdoğan’s government consciously intends to undermine the traditional secularity. This feature is not only a foundation of the state but also a pillar of Turkey’s candidacy to EU. A research method that was used in the article is an analysis of evolution of the principle of separation of state and church in the AKP era based on several decisions made by institutions of public administration. Decisions which were objects of an analysis are inter alia acceptation for presence of Muslim women covering their heads in the public area and tightening the censorship which seems to be only a part of comprehensive political plan consequently implemented by the ruling party.